PEMBERDAYAAN MASYARAKAT ISLAM MELALUI HOME INDUSTRY KERIPIK TEMPE GUNA MENINGKATKAN KESEJAHTERAAN MASYARAKAT (STUDI KASUS DESA LANGSE, KECAMATAN MARGOREJO, KABUPATEN PATI) - Purwati, Dwi (Institut Agama Islam Negeri (IAIN) Kudus, 2021)
The purpose of this study was to determine the empowerment of the Islamic community carried out by the tempe chips home industry in Langse Village, Margorejo District, Pati Regency and how the results obtained by the community after participating in the community empowerment program through the tempe chips home industry in Langse Village, Margorejo District, Pati Regency. carried out by researchers using descriptive research. The research approach used is a qualitative approach. In collecting data, researchers used several techniques, namely, interviews, observation, and documentation. Data analysis in this study includes, Data Reduction, Data Display, Conclusion Drawing/Verification.Based on the research results obtained by the researchers, the researchers stated that: 1) Community empowerment carried out by the tempe chip home industry in Langse Village, Margorejo District, Pati Regency used 3 stages in carrying out its empowerment program, namely the awareness stage, the coaching stage, and the independence stage. 2) The results obtained by the community after participating in the community empowerment program through the tempe chips home industry in Langse Village, Margorejo District, Pati Regency, namely an increase in welfare experienced by the community marked by the freedom of mobility, the ability to buy small commodities, the ability to buy large commodities, being involved in decisions household, the existence of economic security and contribution to the family.